VD_FINDINFO Décision / 2016 / 170 vom 10. März 2016 - VD Tribunal cantonal (2016)
RISQUE DE COLLUSION, RISQUE DE RÉCIDIVE, PROLONGATION, DÉTENTION PROVISOIRE, SOUPÇON | 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH)